SHARE WAQF: ECONOMIC GROWTH AND POVERTY ALLEVIATION IN INDONESIA - Atika Zahra Maulida; Agus Purnomo (IAIN Manado, 2022)
The purpose of empowering business capital taken from profit sharing from Sharia shares managed by the issuer is to encourage economic growth and reduce poverty. In this study, researchers used qualitative methods by conducting interviews with Nazhir, investors, and people in need. The results of the study are as follows: Waqf funds are managed by Nazhir and distributed to capital market products such as sharia shares, sharia mutual funds, Sukuk, SBSN, and others. Profits from share waqf assets will be channeled into economic empowerment activities to provide entrepreneurship training, open job vacancies, and encourage income growth for the community. People who get business capital from Nazhir will be monitored and evaluated based on income growth and business development. The asset management system of share waqf funds distributed is as follows; First, investors and venture capital recipients will agree on both parties regarding the payback period, community capacity, and infaq contributions. The Investment Manager will distribute profits to investors and investors will manage the profits obtained in economic empowerment activities such as entrepreneurship. Profit funds will be given to people in need such as the poor and others and the proceeds from the sale of the resulting products can encourage economic growth and reduce poverty.